2019
DOI: 10.3390/aerospace6030032
|View full text |Cite
|
Sign up to set email alerts
|

Synergy Effects in Electric and Hybrid Electric Aircraft

Abstract: The interest in electric and hybrid electric power system has been increasing, in recent times, due to the benefits of this technology, such as high power-to-weight ratio, reliability, compactness, quietness, and, above all, elimination of local pollutant emissions. One of the key factors of these technologies is the possibility to exploit the synergy between powertrain, structure, and mission. This investigation addresses this topic by applying multi-objective optimization to two test cases — a fixed-wing, ta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 17 publications
0
13
0
Order By: Relevance
“…That is why more and more electric UAVs makes use of hybridization In Figure 2, it can be seen how each technology has very differentiating characteristics in terms of its energy supply capacity. That is why more and more electric UAVs makes use of hybridization among the different technologies [58], taking the benefits of the advantages of each one of them, and adapting to the application for which the electric UAV is designed for [59]. The hybrid combination of different types of energy storage also requires the implementation of larger control systems [60], so that they must reach a balance between energy management alternatives and the size required for computer control equipment, together with the different sensors and actuators that make up the plant balance [61].…”
Section: Fixed-wingmentioning
confidence: 99%
“…That is why more and more electric UAVs makes use of hybridization In Figure 2, it can be seen how each technology has very differentiating characteristics in terms of its energy supply capacity. That is why more and more electric UAVs makes use of hybridization among the different technologies [58], taking the benefits of the advantages of each one of them, and adapting to the application for which the electric UAV is designed for [59]. The hybrid combination of different types of energy storage also requires the implementation of larger control systems [60], so that they must reach a balance between energy management alternatives and the size required for computer control equipment, together with the different sensors and actuators that make up the plant balance [61].…”
Section: Fixed-wingmentioning
confidence: 99%
“…These are relative to the capabilities of a typical new aircraft in 2000. More generally, the aviation industry actually faces the "revolution towards more electric aircrafts" [5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…In a majority of cases, hybrid propulsion system research is conducted for standard fixedwing and vertical takeoff and landing (VTOL) fixed-wing hybrid [4,5], and some other types such as dirigible UAV [6,7]. A detailed analysis of synergetic effects for various classes of UAVs is given in [8] by applying the multi-objective optimization, where results have shown that hybrid-electric configuration has the potential to give a strong contribution to aircraft performance. Moreover, by investigating the behavior of different power sources within the UAV hybrid-electric propulsion system through simulations in order to predict the hybrid electric power system behavior using bench tests, the feasibility and efficiency of the onboard UAV power system can be assessed before the final flight test phase [9].…”
Section: Introductionmentioning
confidence: 99%